Peran Pendidikan Dalam Mengurangi Kesenjangan Gender Di Tempat Kerja - Cahaya Dwi Anggola; Firanica Prawita; Dwi Putri Lestarika (CV. ITTC INDONESIA, 2024)
Gender gap in the workplace is a global issue that is still relevant, with significant impacts on the economy and society. This article discusses the role of education as a strategic tool in reducing gender gaps, focusing on how education can empower women and prepare them for an equal workplace. Through an analysis of various educational programs and policies that have been implemented, this article shows that equal access to quality education can improve women's skills, self-confidence, and employment opportunities. In addition, this article also highlights the importance of gender-sensitive education, which not only educates women but also men about gender equality. By providing recommendations for the integration of inclusive curricula and relevant skills training, this article argues that education is an important foundation in creating a fair and equal work environment. Through collective efforts in education, it is hoped that gender gaps in the workplace can be minimized, thereby promoting more inclusive and sustainable economic growth.